Measuring Stand for Determining the Dynamic Characteristics of the Selected Parameters of Anti-Aircraft Artillery System - Wojciech KACZMAREK; Jacek KIJEWSKI; Paweł DOBRZYŃSKI (Problemy Mechatroniki, 2014)
This paper presents the measuring stand for determining the dynamic characteristics of selected parameters of anti-artillery system during shooting. The stand has been built based on two types of measurement equipment: Xsens of Technologies B.V. company from the Netherlands and the PCB Piezotronics, Inc. company from USA. The proposed solution has enabled the execution of studies related to the acceleration and overload occurring during tests of optoelectronic head of the ZUR-23-2SP set. In addition, the authors presented selected results of the measurements.